Determinants of short and long-term exchange market pressure in Indonesia - Wahyudi, Heru; Palupi, Widia Anggi; Suparta, I Wayan (Jurnal Ekonomi & Studi Pembangunan, 2023)
A decrease in a country's export prices and foreign exchange reserves is symptomatic of exchange rate market pressures, which would be described as an oversupply or disequilibrium in the money market. The method used in this study is the Vector Error Correction Model (VECM) to investigate Exchange Market Pressure (EMP) in Indonesia. This study utilizes secondary data obtained from Statistics Indonesia and Bank Indonesia (BI) website since 2008Q1-2021Q4. The findings of this study demonstrate a strong positive long-term relationship between domestic credit growth and the BI rate, a large negative long-term relationship between GDP growth and the BI rate, and no significant relationship between the current account balance and the exchange rate.